PENGEKANGAN PEREMPUAN MELALUI STANDART-STANDART KELAYAKAN PEREMPUAN - Mega Utami; Nurul Fauziah (Universitas Baturaja, 2024)
This study aims to reveal the representation of women behind the video clip Woman Like Me by Little Mix. This study uses John Fiske's semiotic analysis theory and methods. The collection techniques used in this study were observation on the Woman Like Me video clip, source interviews and literature study. Meanwhile, the subject ofthis research is the women in Little Mix's Woman Like Me video clip while the object of this research is visual communication which includes images, attributes, gestures, sounds and clothes in Little Mix's Woman Like Me video clip. The results of the study show that the Woman Like Me video clip represents women's resistance in achieving gender equality. Women want to fight the restraints on the standards that have been produced and set in society against women. For example; beautiful, elegant, classy, polite, smart and have the skills and ability to do housework. On the other hand, in this video, women are portrayed as brave, independent, free and confiden.